Answer:
(4, 5)
Step-by-step explanation:
Calculate the midpoint using the midpoint formula
midpoint = [( + ), ( + ) ]
with (, ) = (1, 2) and (, ) = (7, 8)
midpoint = [(1 + 7), (2 + 8) ]
= (4, 5)
Answer:
20
Step-by-step explanation:
n(A) only =15-4=11
n(B) only=9-4=5
n(A n B)=4
n(A U B)=11+5+4=20
Answer:
No! The answer is not zero. There can be infinite solutions for this equation.
Hope it helps!
Each of the triangles are equal in base length, height, and area<span>. Remember the formula for the </span>area<span> of a triangle. The </span>area<span> of any triangle is 1/2 times the length of the base (which, in the </span>polygon<span>, is the length of a side) multiplied by the height (which is the same as the apothem in </span>regular polygon<span>).
</span>
Answer:
6 2/7
Step-by-step explanation: